2019
DOI: 10.1158/0008-5472.can-18-1602
|View full text |Cite|
|
Sign up to set email alerts
|

MNK1/NODAL Signaling Promotes Invasive Progression of Breast Ductal Carcinoma In Situ

Abstract: The mechanisms by which breast cancers progress from relatively indolent ductal carcinoma in situ (DCIS) to invasive ductal carcinoma (IDC) are not well understood. However, this process is critical to the acquisition of metastatic potential. MAPK-interacting serine/threonine-protein kinase 1 (MNK1) signaling can promote cell invasion. NODAL, a morphogen essential for embryogenic patterning, is often reexpressed in breast cancer. Here we describe a MNK1/NODAL signaling axis that promotes DCIS progression to ID… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 55 publications
6
29
0
Order By: Relevance
“…) and on-target engagement, as shown by the repression of phospho-eIF4E expression in the melanomas (Figure S7D). These data recapitulate our observations in the phospho-eIF4E deficient BRaf CA/+ /Pten lox/lox (eIF4E KI ) mice, and further supports that systemic inhibition of phospho-eIF4E by blocking MNK1/2, has efficacy in modulating both the tumor and TME in pre-clinical cancer models48,[82][83][84][85] . Strikingly, the combination therapy of SEL201 and anti-PD-1 monoclonal antibody significantly reduced primary melanoma growth, local and distant lymph node metastasis, and increased the overall survival of tumor-bearingBRaf CA/+ /Pten lox/lox mice compared to either of the therapies alone, without causing any overt toxicity (Figure 7C-7F and S7C-S7E).Analysis of plasma cytokine and chemokine levels revealed that the robust anti-tumor effect of SEL201 combined with anti-PD-1 therapy was associated with enhanced peripheral anti-tumor immunity, characterized by a decrease in the immunosuppressive cytokine/chemokine signature, including IL-6, CCL2 and CCL5 (Figure 7H).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…) and on-target engagement, as shown by the repression of phospho-eIF4E expression in the melanomas (Figure S7D). These data recapitulate our observations in the phospho-eIF4E deficient BRaf CA/+ /Pten lox/lox (eIF4E KI ) mice, and further supports that systemic inhibition of phospho-eIF4E by blocking MNK1/2, has efficacy in modulating both the tumor and TME in pre-clinical cancer models48,[82][83][84][85] . Strikingly, the combination therapy of SEL201 and anti-PD-1 monoclonal antibody significantly reduced primary melanoma growth, local and distant lymph node metastasis, and increased the overall survival of tumor-bearingBRaf CA/+ /Pten lox/lox mice compared to either of the therapies alone, without causing any overt toxicity (Figure 7C-7F and S7C-S7E).Analysis of plasma cytokine and chemokine levels revealed that the robust anti-tumor effect of SEL201 combined with anti-PD-1 therapy was associated with enhanced peripheral anti-tumor immunity, characterized by a decrease in the immunosuppressive cytokine/chemokine signature, including IL-6, CCL2 and CCL5 (Figure 7H).…”
supporting
confidence: 88%
“…We EMT plays an important role in tumor immune escape [95][96][97] . In this context, translational control, including the MNK1/2-eIF4E axis, has been implicated in promoting an EMT across different tumor types 10,85,98,99 . Our study links the MNK1/2-eIF4E axis with immune escape of melanoma though an EMT-like phenotype switch.…”
Section: Discussionmentioning
confidence: 99%
“…The data showed a positive correlation between MNK1 activity and the expression of NODAL and vimentin, regulators of invasion and metastasis. MNK1 inhibition with SEL201 could block NODAL signaling to suppress disease [103]. However, all the possible downstream factors and MNK-interactions are yet to be discovered.…”
Section: Mnk In Breast Cancermentioning
confidence: 99%
“…Because fibroblast activation (demarcated by α-SMA expression) and NODAL expression occur early during breast cancer progression 46 , we investigated whether these events could be correlated. We evaluated the expression and localization of NODAL and α-SMA in 41 primary tumour tissue samples from a cohort of 20 TNBC cases ( Table I).…”
Section: Cancer Cells Expressing Nodal Associate With α-Sma-positivementioning
confidence: 99%
“…In breast cancer, NODAL clinically correlates with stage and vascularization 44,45 . Moreover, NODAL expression emerges in breast cancers as they transition from DCIS into IDC 46 , wherein interactions between cancer and stromal cells are critical. NODAL inhibition reduces breast cancer-induced neovascularization and mitigates BCSC frequencies, tumour growth, and invasion [47][48][49] .…”
Section: Introductionmentioning
confidence: 99%